ANALISIS GAYA KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN DESA SUKA MAJU KECAMATAN SUTI SEMARANG KABUPATEN BENGKAYANG - Afra Agriandy; Eligia Monixa Salfarini (Management and Sustainable Development Journal, 2026)
Village development is a strategic effort to improve community welfare and promote equitable national development. The success of village development is determined not only by the availability of resources but also by the leadership style of the village head in managing governance and encouraging community participation. This study aims to analyze the leadership style of the Head of Sukamaju Village in village development in Suti Semarang District, Bengkayang Regency. The research employed a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation involving six participants consisting of the Village Head, the Village Consultative Body (BPD), the Head of Development Affairs, the Hamlet Head, the Neighborhood Head (RT), and a community representative. Data were analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the Head of Sukamaju Village applies a leadership style emphasizing deliberation, participatory decision-making, community involvement, cooperation, transparency, coordination, accountability, and direct engagement with the community. This leadership style has positively contributed to increased community participation, strengthened the culture of mutual cooperation, improved transparency in village governance, and supported the successful implementation of various physical development programs, including clean water reservoirs, suspension bridges, concrete roads, early childhood education facilities, integrated health service posts, the village office, and farm roads. Therefore, democratic and participatory leadership has proven to be effective in supporting sustainable village development.